GAMBARAN KEPATUHAN MINUM OBAT PADA PASIEN DEWASA DENGAN TUBERCULOSIS DI BALAI KESEHATAN PARU MASYARAKAT PURWOKERTO - Pepi Puspasari; Ikit Netra Wirakhmi; Noor Yunida Triana (Bajang Institute, 2025)
Background: Tuberculosis (TB) is a chronic and infectious disease caused by Mycobacterium tuberculosis bacteria and is one of the top 10 causes of death worldwide. TB treatment requires a long duration, 6 months, leading to boredom and discontinuation of treatment. This study aims to determine the description of adherence to medication in adult patients with tuberculosis at the Balai Kesehatan Paru Masyarakat Purwokerto (BKPM). Purpose: This research uses a quantitative method with a descriptive design. Methods: The sample of this study consisted of 76 respondents with total purposive sampling technique. Results: The results showed that the majority of age characteristics were in the late adult category, consisting of 28 respondents (36.8%), female respondents 18 (23.7%), middle education level 30 respondents (39.5%), and unemployed 20 people (26.3%). Adherence to medication in TB patients at BKPM was 48 (63.2%). Conclusion: %). For BKPM Purwokerto, to always provide education about puimonary TB disease so that patients adhere to medication and achieve health